Unions, Worker Participation and Worker Well-Being - Benjamin Artz; John S. Heywood (Global Labor Organization (GLO), 2020)
This chapter focuses on the lessons learned from four decades of studying the relationship between unions and job satisfaction. We discuss the original paradox that started the literature and trace the on-going debate over results that differ by sample and by estimation technique. We emphasize the cross-national evidence suggesting that the paradox of dissatisfied union members may be largely associated with Anglophone countries. Within Anglophone countries we explore exactly what is typically being measured and how unionization may influence both job characteristics and perceptions of given job characteristics. We explore differences in the influence of union membership on job satisfaction and on broader life satisfaction. We also review the literature on alternative forms of employee representation. We conclude by summarizing and suggesting avenues for future research.
Keywords: J31; J32; J51; 330; Job Satisfaction; Unions; Voice; Alternative Representation